Efektivitas Pelatihan Pemasangan Mitella sebagai Intervensi Pertolongan Pertama pada Siswa Sekolah Menengah Atas: Effectiveness of Mitella Placement Training as a First Aid Intervention Among High School Students - Honggu, Anugrah Desi Sari; Magdalena, Gloria Putri; Permatasari, Okta Christie; Pujianingsih, Ribka Elrin; Sianturi, Samgar Julius; Widayati, Stephanie Aurellya Putri; Lerrick, Susana; Suwardianto, Heru (Jurnal Abdi Keperawatan dan Kedokteran, 2026)
Upper limb injuries, particularly involving the arm and shoulder, are common among adolescents in high school settings. Proper first aid management, including the use of a sling (Mitella), is essential to prevent further damage, reduce pain, and support recovery. This study employed a pre–post-test design to evaluate the effectiveness of Mitella placement training among students at SMA 3 Kota Kediri. A total of 32 Grade 1 students were selected using purposive sampling. The training followed a structured Standard Operating Procedure, including theoretical explanation, demonstration, and supervised hands-on practice. Participants’ knowledge was assessed using a 7-item validated questionnaire. Data were analyzed using descriptive statistics and the Wilcoxon Signed Ranks Test. Mitella placement training significantly improved participants’ knowledge(p = 0.008). Most students demonstrated enhanced understanding after the training, indicating that the combination of theory, demonstration, and hands-on practice effectively strengthened their competence. Mitella placement training effectively enhances high school students’ knowledge. These findings support the implementation of practical first aid training programs in schools to improve adolescents’ preparedness and competence in managing upper limb injuries.